Implementation of Logging Feature in Android Payment SDK using Scrum Method - Ardian Dwi Rifai; Erika Ramadhani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Electronic money or e-money is a technological innovation that allows payment transaction processing to be easier and more practical. PT Aino Indonesia is a payment gateway company that serves payment processes using this technology for various business segments. To satisfy the requirements of each business segment, Aino needs to develop a wide range of applications. These applications require a standard for the payment system to make it faster to integrate and maintain. The payment team at Aino has developed a module or SDK that provides a standard payment system for Android-based applications. Two new features will be added to this SDK, the logging feature and log file upload. The logging feature will record the data generated by each transaction process into a log file. Next, the SDK will upload the log files to the server to help retrieve transaction data uploaded from the device. Both features will help the process of tracking issues and problems that may arise during the transaction process. The development of the two features in this SDK uses the Scrum method to ensure it stays on track.